2015
DOI: 10.1073/pnas.1507098112
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal test bed for universal dynamics of phase transitions

Abstract: Early insight on the critical dynamics of phase transitions arose in a cosmological setting in an effort to understand the origin of structure formation in the early Universe. Kibble pointed out that in a spontaneous symmetry breaking scenario, when a system is driven across a phase transition from a high-symmetry phase to a topologically nontrivial vacuum manifold, causally disconnected regions of the system choose independently the broken symmetry (1,2). These conflicting choices result in the formation of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Here a is a constant, φ h the area fraction where the system becomes fully hexatic, and the exponent ν = 1/2 [11,40,41]. As seen in figure 3(b), the data are very well described by this expression and from the fit we obtain a value for φ h = 0.696, which is in excellent agreement with the start of the hexatic phase at φ = 0.70 [36].…”
Section: Bond-orientational Order Correlation Timesupporting
confidence: 68%
See 3 more Smart Citations
“…Here a is a constant, φ h the area fraction where the system becomes fully hexatic, and the exponent ν = 1/2 [11,40,41]. As seen in figure 3(b), the data are very well described by this expression and from the fit we obtain a value for φ h = 0.696, which is in excellent agreement with the start of the hexatic phase at φ = 0.70 [36].…”
Section: Bond-orientational Order Correlation Timesupporting
confidence: 68%
“…Upon approaching the hexatic phase from the liquid, it has been shown that the bond-orientational correlation length diverges [11]. Consequently, it is also expected that the corresponding bond-orientational correlation time, τ 6 , diverges [11,40,41]. We determine τ 6 from the bond-orientational correlation functions g 6 (t), shown in figure 3(a) for a tilt angle of α = 0.25 • [36], via g 6 (t) ∼ exp(−t/τ 6 ).…”
Section: Bond-orientational Order Correlation Timementioning
confidence: 99%
See 2 more Smart Citations
“…A cooling schedule cannot possibly involve the crossing of the critical point considered in the original studies of KZM. However, the KZM prediction can be extended to account for "half-quenches" ending at the critical point [48][49][50][51][52]. At the same time, the finitetemperature treatment endows the dynamic with coarsening.…”
Section: Introductionmentioning
confidence: 99%